Strategi Desain Kemasan Produk Pempek Mozzarella Sebagai Makanan Inovatif Daerah - Luluk Nur Aini; Godham Eko Saputro (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Pempek, a traditional food from South Sumatra has strong potential to be developed through product innovation in order to remain relevant to modern consumer preferences. The innovation of mozzarella-filled pempek requires an appropriate packaging design strategy as a visual communication medium to build consumer perception, attractiveness, and product identity. This study is motivated by the limited effectiveness of packaging design strategies for innovative local food product in integrating local identity with modern visual aesthetics. The purpose of this study is to formulate a packaging design strategy for mozzarella pempek based on a visual communication design approach. A descriptive quantitative method was employed, with data collected through questionnaires to identify consumer perception, visual preferences, and evaluations of packaging design elements, complemented by expert validation using the Aiken’s V method. The results indicate that the packaging design strategy achieved a high level of attainment, emphasizing visual clarity, modern design style, attractive color selection, informative typography, and the integration of local cultural elements as visual identity. Expert validation results show that all indicators fall within the valid to highly valid categories (V ≥ 0.75), confirming that the packaging design strategy has adequate content validity. This study concludes that packaging design strategy plays a crucial role as a visual communication medium in shaping positive consumer perception of mozzarella pempek as an innovative local food products